Deciphering the Dynamics of EGFR-TKI Resistance in Lung Cancer: Insights from Bibliometric Analysis - Zhou Y; Wu T; Sun J; Bi H; Xiao Y; Shao Y; Han W; Wang H (Dove Medical Press, 2024)
Yinxue Zhou,1,* Tingyu Wu,2,* Jiaxing Sun,1 Huanhuan Bi,1 Yuting Xiao,1 Yanmei Shao,1 Weizhong Han,1 Hongmei Wang1 1Department of Respiratory and Critical Care Medicine, The Affiliated Hospital of Qingdao University, Qingdao, People's Republic of China; 2Department of Joint Surgery, The Affiliated Hospital of Qingdao University, Qingdao, People's Republic of China*These authors contributed equally to this workCorrespondence: Jiaxing Sun; Hongmei Wang, Email jiaxing20022001@163.com; dor.whm@163.comBackground: EGFR-TKI resistance poses a significant challenge in the treatment landscape of non-small cell lung cancer (NSCLC), prompting extensive research into mechanisms and therapeutic strategies. In this study, we conduct a bibliometric analysis to elucidate evolving research hotspots and trends in EGFR-TKI resistance, offering insights for clinical interventions and scientific inquiries.Methods: Publications spanning from 1996 to 2024, focusing on EGFR-TKI resistance in NSCLC, were sourced from the Web of Science Core Collection. Utilizing VOSviewer 1.6.19, CiteSpace 6.2. R2, and Scimago Graphica 1.0.35, we analyzed these articles to identify countries/regions and institutions, Journals, publications, key contributors, collaborations, and emerging topics.Results: An analysis of 8051 articles by 38,215 researchers from 86 countries shows growing interest in EGFR-TKI resistance mechanisms. Since 1996, publications have steadily increased, surpassing 500 per year after 2016, with a sharp rise in citations. Research articles make up 84% of publications, emphasizing scholarly focus. Global collaboration, especially among researchers in China, the US, and Japan, is strong. Leading institutions like Dana-Farber and Harvard, along with journals such as "Lung Cancer", are key in sharing findings. Professors Yi-Long Wu and William Pao are prominent contributors. Keyword analysis reveals core themes, including first-generation EGFR-TKIs, emerging agents like osimertinib, and research on the T790M mutation.Conclusion: EGFR-TKI resistance remains a critical issue in NSCLC treatment, driving ongoing research efforts worldwide. Focusing future research on clear identification of resistance mechanisms will guide post-resistance treatment strategies, necessitating further exploration, alongside the validation of emerging drugs through clinical trials. Moreover, "chemo+" treatments following EGFR-TKI resistance require more clinical data and real-world evidence for assessing safety and patient outcomes. As research advances, a multidisciplinary approach will be key to overcoming these challenges. Continued innovation in treatment could greatly enhance patient survival and quality of life.Keywords: EGFR-TKI, resistance, lung cancer, bibliometric, citespace, VOSviewer